Strenght in Partnership: How Husband’s Support Relate to Maternal Anxiety in Child Care - Dyah Titisari; Tina Mawardika (GLOBAL HEALTH SCIENCE GROUP, 2025)
Pregnant women are often filled with anxiety, especially those who are pregnant for the first time, especially before labor. Mothers about to give birth experience excessive emotions, leading to high levels of anxiety, a state where they constantly think about potential negative outcomes. The lack of social support can exacerbate the emotional and physical burden on mothers. Many new mothers feel unprepared regarding infant care, breastfeeding, and infant sleep patterns. This study aimed to examine the relationship between husband’s support and maternal anxiety in facing childbirth. This can lead to feelings of insecurity and stress in their new role as mothers. This study used a quantitative cross-sectional design. This study analyzed the relationship between husband's support and anxiety levels. The population of pregnant women in their third trimester in the Bancak Community Health Center (Puskesmas) working area was 75 respondents in the last three months of January 2025. A sample of 63 respondents was obtained. The researcher used a questionnaire as an instrument. This study utilized univariate and bivariate data analysis. The Rank Spearman statistical test yielded a p-value of 0.000 < α (0.05). Therefore, it can be concluded that there is a relationship between husband's support and the level of anxiety facing childbirth in the Bancak Community Health Center area. There is a relationship between husband's support and the level of anxiety facing childbirth.